(untitled) (Jurnal Riset Agribisnis dan Peternakan, 2022)
Eggs stored at room temperature are easily damaged. The pores in the shell allow microorganisms to enter. This study aims to determine the levels of tannins at different levels of teak leaves and guava leaves. The materials included 60 eggs, teak leaves, guava leaves, and salt. The treatments given were 0:100 (B0J100), 25:75 (B25J75), 50:50 (B50J50), 75:25 (B75J25), and 100:0 (B100J0). This study used a Completely Randomized Design Factorial (CRD) with 5x4 with 4 replications. The first factor was the level of guava and teak leaves with a ratio of 0:100, 25:75, 50:50, 75:25 and 100:0. The second factor is storage time consisting of L1 = 0th day, L2 = 5th day, L3 = 10th day and L4 = 15th day. The results showed that the tannin levels of teak leaves and guava leaves were relatively the same, ranging from 0.0132 to 0.0235. The Total Plate Count value of boiled eggs had a significant effect (P≤0.05) with Total Plate Count values ​​ranging from 5.68x106 to 5.35x108. The conclusion is that there is an effect of adding teak and guava leaves to the Total Plate Count test, while the tannin content of boiled eggs is relatively the same. Suggestions to increase the concentration level so that the shelf life is longer.